(untitled) (Menara Perkebunan, 2026)
The rising global demand for palm oil necessitates innovative strategies to accelerate yield improvement and ensure sustainable production. Conventional propagation methods are limited by long regeneration cycles, making tissue culture a more practical alternative that relies on elite ortet identification. This preliminary study aimed to evaluate crude palm oil quality, leaf metabolite profiles, and gene expression as early indicators for selecting elite ortets. Mature fruits were used to assess oil yield, free fatty acid, and β-carotene contents, while leaves were analyzed for chlorophyll and total phenolic content. Based on biochemical screening, three candidate ortets were further evaluated for the expression of acetyl-CoA carboxylase (ACCase) and phytoene synthase (PSY) genes. Oil yield ranged from 77-83%, FFA 5-9%, and β-carotene 200-450 mg kg-1 CPO across candidates. Candidate 3.7 exhibited the highest oil yield and elevated ACCase expression, while candidate 6.12 showed the highest β-carotene content and PSY expression. Candidate 5.7 demonstrated relatively low FFA and favorable chlorophyll levels. These results suggest an association between ACCase expression and oil yield, as well as between PSY expression and β-carotene accumulation. Collectively, these findings support a proof-of-concept for an integrated profiling strategy to select elite ortets for advanced tissue culture propagation.